The labor right of minors - Vargas Álvarez, Jenny Cecilia (2007)
Studies have determined that the minors are forced to work because of the emptiness and contradictions of our law as well as by factors of violence, poverty, etc. In that sense the present article in the first part intent to explain the concept of the children and adolescent rights from the liberalist and protectionistic school point of view. In the second part explains which are the national and international normative instruments that are helpful for the protection of the children and adolescents rights. The article ends with and analysis of the work condition in our country